METHODS OF FORMING CRITICAL THINKING IN STUDENTS - Ikromova Sitora Akbarovna (Economics, management, and digital innovation in education: contemporary trends and approaches, 2025)
This The article is critical of readers. thinking of formation current aspects of it training in the process importance and effective method and approaches illuminating given . Critical thinking is​ students independent decision acceptance to do , to evidence relying on analysis to do , various thoughts assessment and to justify instructor important from competencies is one . In the study school in their classes critical thinking to develop aimed at methods analysis will be done and their in practice review of application experiences is released .